A comparison of linkage to HIV care after provider-initiated HIV testing and counselling (PITC) versus voluntary HIV counselling and testing (VCT) for patients with sexually transmitted infections in Cape Town, South Africa - Leon, Natalie (BioMed Central, 2014)
BACKGROUND: We examined linkage to care for patients with sexually transmitted infection who were diagnosed HIV-positive via the provider-initiated HIV testing and counselling (PITC) approach, as compared to the voluntary counselling and testing (VCT) approach, as little is known about the impact of expanded testing strategies on linkage to care. METHODS: In a controlled trial on PITC (Cape Town, 2007), we compared HIV follow-up care for a nested cohort of 930 HIV-positive patients. We cross-referenced HIV testing and laboratory records to determine access to CD4 and viral load testing as primary outcomes. Secondary outcomes were HIV immune status and time taken to be linked to HIV care. Logistic regression was performed to analyse the difference between arms. RESULTS: There was no difference in the main outcomes of patients with a record of CD4 testing (69.9% in the intervention, 65.2% in control sites, OR 0.82 (CI: 0.44-1.51; p = 0.526) and viral load testing (14.9% intervention versus 10.9% control arm; OR 0.69 (CI: 0.42-1.12; p = 0.131). In the intervention arm, ART-eligible patients (based on low CD4 test result), accessed viral load testing approximately 2.5 months sooner than those in the control arm (214 days vs. 288 days, HR: 0.417, 95% CI: 0.221-0.784; p = 0.007). CONCLUSION: The PITC intervention did not improve linkage to CD4 testing, but shortened the time to viral load testing for ART-eligible patients. Major gaps found in follow-up care across both arms, indicate the need for more effective linkage-to-HIV care strategies. TRIAL REGISTRATION: Current Controlled Trials ISRCTN93692532 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1472-6963-14-350) contains supplementary material, which is available to authorized users.